Heath risk assessment of heavy metals in prawn Penaeus merguiensis collected in 2007 from Sri Serdang market, Peninsular Malaysia - Yap, Chee Kong; Cheng, Wan Hee; Ali, Mohd Hafetz; Nulit, Rosimah; Peng, Shih Hao Tony; Ismail, Mohamad Saupi; Leow, Chee Seng (Acta Scientific, 2019)
Samples of prawn (Penaeus merguiensis), were collected from a market in Serdang, Selangor, Peninsular Malaysia, in 2007. The prawns samples were dissected into five parts; soft tissue, carapace, periopods, pleopods and telson. The mean metal concentrations (µg/g dry weight) in the soft tissues of the prawns were 89.2 for Fe, 13.6 for Cu, 55.5 for Zn, 0.01 for Cd and 0.01 for Ni. For the human health risk assessment, all values of target hazard quotient for the five metals in the adults of Malaysian population were found below 1.00. This showed that there was no non-carcinogenic risk of the five metals via the consumption of P. merguiensis from the present study. Still, it is highly recommended that frequent monitoring of toxic chemicals besides heavy metals should be carried out for possible chemical contamination in this popular seafood in Malaysia.